The economic response of rural areas to local supply shock: evidence from the Occupied West Bank - Fallah, Belal (Middle East Development Journal, 2018)
As the Second Intifada broke out at the end of 2000, Israel severely restricted entry for Palestinians to its labor market, forcing a great section of commuters to return to their local labor markets. This paper examines the economic effect of the return commuting on non-commuters in rural areas of the Occupied West Bank. Utilizing place-of-work, repeated cross-section data, the results show that returned commuting has negative repercussions. Specifically, wages decrease for workers with the same skill type (low skilled). The results also provide evidence that favors the crowd-out effect hypothesis. The estimated probability of unemployment increases for non-commuters with disproportionate effect for job seekers relative to those reportedly employed. Consistent with this result, increases in return commuting prolong unemployment duration for the low skilled. The outcome of this paper helps understand how rural labor markets may respond to labor supply shocks.
Keywords: Return commuting; local labor supply shock; wages; unemployment